Effect of Corruption on Tax Revenues in the Middle East - Imam, Patrick (IMF Working Papers; Working Paper ;, 2007)
This study estimates the impact of corruption on the revenue-generating capacity of different tax categories in the Middle East. We find that the low revenue collection as a share of GDP there compared to other middle-income regions is due in part to corruption, and certain taxes are more affected than others. Taxes that require frequent interaction between the tax authority and individuals, such as taxes on international trade, seem to be more affected by corruption than most other types of taxation. This suggests that if governments need to raise more tax revenues in a way that minimizes distortions and maximizes social welfare, they should implement reforms that either reduce corruption or raise revenues from tax categories that are less susceptible to corruption. Possible reforms of the revenue system and administration are examined.